1978
DOI: 10.1111/jpc.1978.14.3.182
|View full text |Cite
|
Sign up to set email alerts
|

A Syndrome of Mental Retardation, Wide Mouth and Intermittent Overbreathing

Abstract: Pitt, D. and Hopkins, I. (1978). Aust. Paediatr. J., 14, 182–184. A syndrome of mental retardation: wide mouth and intermittent overbreathing. Two retarded children are described, with similar facies, consisting of an unusually wide mouth and palate, thick fleshy lips, and a broad‐beaked nose. They also had an unusual respiratory rhythm, clubbing of the fingers, and abnormal electroencephalograms. This may represent a new syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 1 publication
3
104
0
2
Order By: Relevance
“…13,14 Homozygous TCF4 deletion in mice lead to early lethality of unknown reason, 15 suggesting an essential role for E2-2 factors in development. In addition, genetic studies have recently demonstrated that loss of one copy of TCF4 in human causes the Pitt-Hopkins syndrome, [16][17][18] a neurodevelopment disease characterized by mental retardation, seizures and hyperventilation, 19 supporting an essential role for E2-2 factors in human nervous system development. In fact, it has been observed that E2-2 forms functional heterodimers with the bHLH factors HASH-1 and MATH1, involved in development of specific parts of the central and peripheral nerves.…”
Section: 12mentioning
confidence: 99%
“…13,14 Homozygous TCF4 deletion in mice lead to early lethality of unknown reason, 15 suggesting an essential role for E2-2 factors in development. In addition, genetic studies have recently demonstrated that loss of one copy of TCF4 in human causes the Pitt-Hopkins syndrome, [16][17][18] a neurodevelopment disease characterized by mental retardation, seizures and hyperventilation, 19 supporting an essential role for E2-2 factors in human nervous system development. In fact, it has been observed that E2-2 forms functional heterodimers with the bHLH factors HASH-1 and MATH1, involved in development of specific parts of the central and peripheral nerves.…”
Section: 12mentioning
confidence: 99%
“…TCF4 is critical for normal brain development (Flora et al, 2007). Human haploinsufficiency of TCF4 may result in severe cognitive deficiency (ie, mental retardation) in patients with Pitt-Hopkins syndrome (Pitt and Hopkins, 1978) or Angelman syndrome (Takano et al, 2010). However, the role of the TCF4 gene in cognitive deficiency in SCZ patients has seldom been studied (for exceptions, see Lennertz et al (2011); Quednow et al (2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Second, several studies showed that TCF4 haploinsufficiency contributes to severe neurodevelopmental disorders such as the Pitt-Hopkins syndrome [1,4,9,33,40]. This autosomal dominant encephalopathy is characterized by severe mental retardation, microcephaly, disrupted motor development, and hyperventilation, as described above [25]. Third, animal studies showed that TCF4 knock-out mice die within 24 hours after birth [13].…”
Section: Tcf4 and Cognitive Endophenotypes Of Schizophreniamentioning
confidence: 87%
“…In 2007, disruption of the TCF4 gene was shown to cause Pitt-Hopkins syndrome [1,4,40]. Pitt-Hopkins syndrome was described in 1978 as a syndrome of mental retardation, microcephaly, facial dysmorphisms, and intermittent hyperventilation [25]. Seizures also frequently occur in the syndrome [33].…”
Section: Introductionmentioning
confidence: 99%